Crítica dos estudos do território : para além de antinomias e metáforas - Nunes, Pedro Paulo de Lavor (2021)
A significant fraction of geographers in Brazil, most present in the last forty years, has produced conceptual studies of the territory based on liberal and irrationalist conceptions, under the cover of “plurality” and a “relational approach”, aiming to meet the perspectives aimed at territoriality studies and projects and plans invested at the local scale, as well as supporting and legitimizing various liberal public discourses and policies under the interest of the bourgeoisie. Among such studies, the studies carried out by Rogério Haesbaert in Brazil stand out, both for the amount of research that uses it as a basic theoretical foundation, and for the theoretical effort in conceptualizing / problematizing the territory, combining antinomies and spatial metaphors, of what he relates between concrete-functional and symbolic-identity processes. If, on the one hand, the concept of territory as a locality, territoriality or place was (re) valued, on the other, there was a complete trivialization of economic-political issues, severely reducing the debate about conflicts, the domination of certain social classes over the others, the active character of the bourgeois state and the multiple relations and determinations encompassed in the totality of the capitalist production of space. This thesis proposes a fundamental ontological reflection for the criticism of Haesbaert's epistemological studies on the territory, in the commitment to contribute with a theoretical-methodological orientation to understand the social reality in spaces of territorial appropriation and domination. Thus, space, dialectics, materiality, spatial scales and totality will be procedurally evidenced, from the perspective of the materialist conception of history, supported by the triad critical-reflexive-operational direction. The method of analysis that guided this research and the writing of all the doctoral work is dialectical historical materialism. Therefore, like the method devised by Marx, the study of the contradictory real was carried out through criticism of the fundamentals and theoretical movements before liberal conceptions and denial of the transformation of the world. In the midst of the denial of revolutionary praxis, poststructuralist and post-modern geographers prolong Foucault's understanding of the universalization of the fragmentary “power relations” for the field of Geography. And so, in reproducing a distorted conception of history or a total abstraction from it, Haesbaert (as a representative of the studies of the territory in Brazil) in his thought production process has converted dialectical contradictions into antinomies and elevated isolated moments of a contradictory totality in spatial metaphors. In criticizing the post-structuralist and post-modern assumptions, here we advocate a Geography committed to social transformation, beyond antinomies and metaphors of a science aimed at reproducing the liberal logic and promoting policies for the reproduction of capital. A Geography that besides denouncing the contradiction between the world of appearances and consumption and the irrationality present in society as a whole, can also proclaim what liberal conceptions have tried to destroy: the issues of the struggle for another society and real human freedom.________________________________________________________________________________________________________________________________